Additional data supporting the 2022 updates to the ISO 5167 standards. (August 2022) - Collins, Alistair; Clark, Steve
Abstract: This paper describes some of the revisions due to be published in the 2022 issue of the ISO 5167 standards documents. The additional data from the authors' company supporting these updates is described to provide context, and to give users of these standards greater assurance of their underlying reliability. Highlights: Revisions to the ISO 5167 standards (due to be published in 2022) are detailed. Additional data is described to provide context to those revisions. Future work is also suggested to update the relevant ISO/TC 30/SC 2 documents that support these standards.